The Development of the Intercultural Competence in Young Learners in an Elementary School in Miami - Ordones, Damary (International Journal of Language and Literary Studies, 2021)
In 1951, Jean Piaget and Anne Marie Weil analyzed the way in which children perceived foreigners in their article, “The Development in Children of the Idea of Homeland and of Relations with other Countries”. They concluded that only at the age of 11 or 12, did they reach the affective and cognitive development to understand and relate to people from other countries. The results of my work go beyond these studies, unlike what happens in a multilingual society, such as Switzerland where Piaget and Weil’ research is contextualized. Children in a multicultural society like Miami, Florida, develop the cognitive and affective aspects to relate to others at an earlier age. I applied two methodologies to this study. The first method is a questionnaire divided into three parts: 1) the development of the concept of homeland in children, 2) their reaction towards countries other than their own, and 3) the cognitive and affective understanding of others. The second method consisted of didactic lessons designed to fosterand enhance students’s intercultural competence and their acquisition of a foreign language.